BMP-2 and ?-Tocopherol Loaded Nanofiber Coatings for Dental Implants: In Vitro and In Vivo Evaluation of Osseointegration - Tezel, Huseyin; Karatas, Esra; Bozoglan, Alihan; Dundar, Serkan; Nizam, Nejat; Armagan, Guliz; Karasulu, H. Yesim (Springer, 2025)
The durability of dental implants depends on successful osseointegration, which can be improved by advanced drug delivery systems enabling controlled bioactive release. In this study, titanium dental implants were coated with nanofibers containing bone morphogenetic protein-2 (BMP-2) and alpha-tocopherol using the electrospinning method to achieve sustained therapeutic effects. BMP-2 was encapsulated within poly(lactic-co-glycolic acid) (PLGA) nanoparticles to regulate its release profile, while alpha-tocopherol was directly incorporated into the polymer matrix to enhance stability and bioactivity. The coated implants were systematically characterized in vitro regarding their biocompatibility, osteogenic differentiation potential, and inflammatory response. For in vivo evaluation, the coated implants were surgically implanted into the tibias of Wistar albino rats. Following a 30-day period, histopathological and biochemical assessments were conducted to analyze bone integration and inflammatory response. Toluidine Blue staining and microscopic imaging revealed improved bone-implant bonding and increased bone volume fraction (BVF) around the coated implants, indicating enhanced osseointegration. Additionally, bone-to-implant contact (BIC) and bone filling (BF) analyses demonstrated a significant improvement in bone integration compared to uncoated implants. Analyses of inflammatory markers, including C-reactive protein (CRP) and interleukin-1 beta (IL-1 beta), confirmed that the formulation did not induce an adverse inflammatory response. These findings highlight the potential of BMP-2 and alpha-tocopherol-loaded nanofiber coatings as a promising drug delivery strategy to optimize implant integration and accelerate bone healing, offering a controlled release approach for clinical applications.
Keywords: BMP-2; alpha-tocopherol; Osseointegration; Dental implants; Nanofiber coating; Poly(lactic-co-glycolic acid) (PLGA)